2018
DOI: 10.3390/nu10111733
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Supplement Use among the Chinese Population: A Cross-Sectional Study of the 2010–2012 China Nutrition and Health Surveillance

Abstract: Nutrient supplements play a key role in managing malnutrition/chronic diseases and are commonly used in the world, but few studies described the prevalence of nutrient supplement use at the national level in China. To our knowledge, this study provides the first detailed investigation of nutrient supplement use in a nationally representative sample of the Chinese population. This study aimed to describe the prevalence of the nutrient supplement use among the Chinese population aged 6 years or older in 2010–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 46 publications
7
64
4
3
Order By: Relevance
“…However, other studies reported only minor differences between the total vitamin D and Ca intakes (including dietary and supplemental sources) and the intakes attributable solely to dietary sources (26,47) . Moreover, it was reported that in China, only 0•19-1•01 % and 0•24-1•19 % of adults took vitamin D and Ca supplements, respectively (66) . Fifth, the present study did not measure serum 25-hydroxyvitamin D level which is a marker of systemic vitamin D exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies reported only minor differences between the total vitamin D and Ca intakes (including dietary and supplemental sources) and the intakes attributable solely to dietary sources (26,47) . Moreover, it was reported that in China, only 0•19-1•01 % and 0•24-1•19 % of adults took vitamin D and Ca supplements, respectively (66) . Fifth, the present study did not measure serum 25-hydroxyvitamin D level which is a marker of systemic vitamin D exposure.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, studies investigating the prevalence of malnutrition amongst adults and elderly in China and Vietnam are lacking. However, in a Chinese study on nutrient supplement use, malnutrition was recognized as Bdouble burden,^meaning overweight and chronic diseases in urban and rural areas on the one hand, and stunting and underweight amongst poor rural residents on the other hand [31].…”
Section: Discussionmentioning
confidence: 99%
“…Test Kit (HybriBio Ltd), and cases were divided into the high-risk HPV infection group and "others" (including low-risk HPV and negative cases). This assay can identify 21 6,11,42,43,44, and CP8304, which were identi ed using the ow-through hybridization technique performed with a TC-96/G/H6 HPV DNA Ampli cation Analyzer and an HMM-2 fast nucleic acid molecule hybridization instrument (HybriBio Ltd).…”
Section: Hpv Genotyping By Hybrimax Was Performed Using Residual Pap mentioning
confidence: 99%
“…The nutrition values from all other FFQ items were combined to obtain the total daily nutrition values. However, we did not collect the dietary supplement information in this study because the prevalence of nutrients supplement use is very low in Chinese population [42]. We estimated the level of each dietary nutrient intake as the following equation: Total daily nutrition value = total amount of each food (g/mg/µg) / (day)* intake value per 100 g, per 100 mg, and per 100 µg.…”
Section: Dietary Nutrient Assessmentmentioning
confidence: 99%